Effects of boundary conditions on coherent synchrotron radiation in echo-enabled harmonic generation - Dmitrii Samoilenko; Demin Zhou; Najmeh Mirian; Wolfgang Hillert; Pardis Niknejadi (Physical Review Accelerators and Beams)
Coherent synchrotron radiation (CSR) is known for its detrimental effects on the performance of free electron lasers (FEL). While it is commonly considered a source of beam quality degradation in linacs, in externally seeded FEL schemes, CSR is known to spoil the bandwidth of the FEL radiation. Investigating CSR’s effect on seeded FELs requires a realistic estimation of CSR-induced energy modulations, known as wakes. Several models exist for calculating CSR wakes, differing in their treatment of transient and shielding effects. This work applies various models to compute CSR wakes in a magnetic chicane. In particular, it highlights the importance of the chicane chamber shielding for relatively long electron bunches used in seeded FELs. We use the practical example of the echo-enabled harmonic generation (EEHG) seeding technique to establish that proper consideration of transient and shielding effects is essential for estimating the impact of CSR on seeded FEL performance. This corrected estimate is vital for reaching the near-Fourier limit bandwidth of EEHG by the currently available methods.